The legal economic effects of maritime piracy - Cavin Willy Mohonis Sambenthiro; Imam Fadhil Nugraha (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Maritime piracy has long been a significant threat to global shipping, with profound economic and legal implications. This journal explores the economic effects and legal actions associated with maritime piracy. The economic impact of piracy is substantial, costing the international economy between $7 billion and $12 billion annually. The rise in piracy has led to higher ransom demands, with some payments reaching record amounts, and has significantly increased the cost of maritime insurance, particularly in high-risk zones. From a legal perspective, the journal examines the evolution of piracy laws, highlighting the United Nations Convention on the Law of the Sea (UNCLOS) and its definition of piracy. The legal framework under UNCLOS includes three main elements: acts committed for private ends, occurring on the high seas, and involving two ships. The journal also discusses the concept of universal jurisdiction, which allows any state to prosecute pirates, though prosecution must follow the domestic laws of the capturing state.The International Maritime Organization (IMO) has introduced several conventions and initiatives, such as the Djibouti Code of Conduct, to enhance maritime security. This journal will focus on the economical effect and the suitable legal actions to punish and prevent the acts of piracy.